Clinical parameters outweigh diffusion- and perfusion-derived MRI parameters in predicting survival in newly diagnosed glioblastoma - Burth, Sina; Vollmuth, Philipp; Eidel, Oliver; Tichy, Diana; Bonekamp, David; Weberling, Lukas D.; Wick, Antje; Löw, Sarah; Berberich, Anne; Nowosielski, Martha; Schlemmer, Heinz-Peter; Wick, Wolfgang; et al. (Neuro-Oncology, 2016)
AbstractBackground. The purpose of this study was to determine the relevance of clinical data, apparent diffusion coefficient (ADC), and relative cerebral bloo